1985
DOI: 10.1002/j.1939-4640.1985.tb00834.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Testicular Function Induced by Hyperprolactinemia in the Rat

Abstract: The effects of hyperprolactinemia on testicular structure and pituitary-gonadal function were investigated in male rats. Hyperprolactinemia was induced in the Wistar-Furth rat by implantation of tissue fragments of a prolactin-secreting MtTW15 pituitary adenoma. The MtTW15 tissue was maintained in one animal group for 27 days (group A) and in another group for 37 days (group B). Appropriate age-matched controls were utilized in each study. Serum prolactin was significantly elevated (P less than 0.001) in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Our studies on the model of hyperprolactinaemia induced by MCP have confirmed information disclosed previously (Cameron et al, 1984;Katovich et al, 1985), namely that exfoliation of spermatogenic cells from the seminiferous tubules occurs. Our findings also confirmed previous observations that in hyperprolactinaemia, provoked by either MCP application or any other factors, the number of spermatozoa in the ejaculate is reduced (Segal et al, 1979;Rocco et al, 1983;Yousef et al, 1989).…”
Section: Discussionsupporting
confidence: 91%
“…Our studies on the model of hyperprolactinaemia induced by MCP have confirmed information disclosed previously (Cameron et al, 1984;Katovich et al, 1985), namely that exfoliation of spermatogenic cells from the seminiferous tubules occurs. Our findings also confirmed previous observations that in hyperprolactinaemia, provoked by either MCP application or any other factors, the number of spermatozoa in the ejaculate is reduced (Segal et al, 1979;Rocco et al, 1983;Yousef et al, 1989).…”
Section: Discussionsupporting
confidence: 91%
“…A homeostasis of plasma PRL is crucial for a normally functioning reproductive system. However, abnormally elevated plasma PRL levels for a long period of time are harmful for the gonadal functions [Katovich et al, 1985;Sharpe and McNeilly, 1980;Waeber et al, 1983].…”
Section: Discussionmentioning
confidence: 99%
“…Prolactin regulates the number and sensitivity of LH receptors within Leydig cells. Although the evidence is not entirely uniform within a species, increased PRL concentrations have been generally reported to have suppressive effects on GnRH release, T levels, copulatory behavior, and degenerative effects on testicular spermatogenesis in many species, including the rat and man (Aleem et al 2005;Katovich et al 1985;Perryman and Thorner 1981). However, the opposite effect has been demonstrated in the mouse, with increased levels of gonadotropins (LH and FSH), increased copulatory behavior, and enlargement of ASOs (Bartke et al 1987;Wennbo et al 1997).…”
Section: Hormonally Mediated Morphologic Changes In the Ratmentioning
confidence: 99%